Focal salvage treatment for radiorecurrent prostate cancer: A magnetic resonance-guided stereotactic body radiotherapy versus high-dose-rate brachytherapy planning study. (July 2020) - Willigenburg, Thomas; Beld, Ellis; Hes, Jochem; Lagendijk, Jan J.W.; de Boer, Hans C.J.; Moerland, Marinus A.; van der Voort van Zyp, Jochem R.N.
Highlights: SBRT may provide a non-invasive treatment option for recurrent prostate cancer. MR-Linac single fraction 19 Gy treatment of recurrent prostate cancer is feasible. MR-Linac dose distributions for the target were comparable to HDR-brachytherapy. Real-time intrafraction adaptation techniques are needed for clinical introduction. Abstract: Background and Purpose: Magnetic resonance imaging (MRI)-guided focal salvage high-dose-rate brachytherapy (FS-HDR-BT) is one of the treatment options for radiorecurrent localized prostate cancer. However, due to the invasive nature of the treatment, not all patients are eligible. Magnetic resonance linear accelerator (MR-Linac) systems open up new treatment possibilities and could potentially replace FS-HDR-BT treatment. We conducted a planning study to investigate the feasibility of delivering a single 19 Gy dose to the recurrent lesion using a 1.5 Tesla MR-Linac system. Materials and Methods: Thirty patients who underwent FS-HDR-BT were included. The clinical target volume (CTV) encompassed the visible lesion plus a 5 mm margin. Treatment plans were created for a 1.5 Tesla MR-Linac system using a 1 mm planning target volume (PTV) margin. A dose of 19 Gy was prescribed to ≥ 95% of the PTV. In case this target could not be reached, i.e. when organs-at-risk (OAR) constraints were violated, a dose of ≥ 17 Gy to ≥ 90% of the PTV was accepted. MR-Linac plans were compared to clinical FS-HDR-BT plans. Results: Target dose coverage was achieved in 14/30 (47%) FS-HDR-BT plans and 17/30 (57%) MR-Linac plans, with comparable median D95% and D90%. In FS-HDR-BT plans, a larger volume reached ≥ 150% of the prescribed dose. Urethra D10%, rectum D1cm 3, and rectum D2cm 3 were lower in the FS-HDR-BT plans, while bladder dose was comparable for both modalities. Conclusion: Single fraction treatment of recurrent prostate cancer lesions may be feasible using stereotactic body radiotherapy (SBRT) on a MR-Linac system.